Cellular signalling of non‐synonymous single‐nucleotide polymorphisms of the human μ‐opioid receptor (OPRM1). (1st July 2014) - Knapman, Alisa; Connor, Mark
<x xml:space="preserve">Abstract</x> There is significant variability in individual responses to opioid drugs, which is likely to have a significant genetic component. A number of non‐synonymous single‐nucleotide polymorphisms (SNPs) in the coding regions of the μ‐opioid receptor gene (OPRM1) have been postulated to contribute to this variability. Although many studies have investigated the clinical influences of these μ‐opioid receptor variants, the outcomes are reported in the context of thousands of other genes and environmental factors, and we are no closer to being able to predict individual response to opioids based on genotype. Investigation of how μ‐opioid receptor SNPs affect their expression, coupling to second messengers, desensitization and regulation is necessary to understand how subtle changes in receptor structure can impact individual responses to opioids. To date, the few functional studies that have investigated the consequences of SNPs on the signalling profile of the μ‐opioid receptor in vitro have shown that the common N40D variant has altered functional responses to some opioids, while other, rarer, variants display altered signalling or agonist‐dependent regulation. Here, we review the data available on the effects of μ‐opioid receptor polymorphisms on receptor function, expression and regulation in vitro, and discuss the limitations of the studies to date. Whether or not μ‐opioid receptor SNPs contribute to individual variability in opioid responses remains an open question, in large part because we have relatively little good data about how the amino acid changes affect μ‐opioid receptor function. Linked Articles This article is part of a themed section on Opioids: New Pathways to Functional Selectivity. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-2